The Concept of Digital-Based Islamic Religious Education at the Elementary Madrasah (MI) Level - Arifin, Zaenal ‘; Indra, Hasbi; Bahruddin, E.; Handrianto, Budi (Formosa Journal of Sustainable Research, 2024)
The presence of advanced technology today, such as Artificial Intelligence (AI), has yet to be fully utilized in the primary education sector in Indonesia. Many schools have the means to provide such technological facilities. Thus, teaching using conventional methods or without the aid of Information Technology (IT) tools cannot accelerate effective and efficient digital-based Islamic Religious Education (PAI) learning in Madrasah Ibtidaiyah (MI)and formulate an ideal concept for digital-based PAI learning at the MI level. The research methodology used is descriptive qualitative research, collecting data through participant observation, in-depth interviews, and documentation.The study results indicate that the concept of digital-based Islamic Religious Education (PAI) learning at the MI. Ideal, effective, and efficient digital-based PAI learning at the MI level, aligned with national educational goals, involves face-to-face learning balanced with digitalization across objectives, standardized materials, methods, and evaluation. These aspects must be integrated with Islamic values, encompassing affective, cognitive, and psychomotor domains, which include knowledge, skills, and attitudes